The global prevalence of oropharyngeal dysphagia in different populations: a systematic review and meta-analysis - Fatemeh Rajati; Nassim Ahmadi; Zahra Al-sadat Naghibzadeh; Mohsen Kazeminia (Journal of Translational Medicine, 2022)
Abstract Background Oropharyngeal dysphagia (OD) refers to any abnormality in the physiology of swallowing in the upper gastrointestinal tract, which leads to the related clinical complications, such as malnutrition, dehydration, and sever complication, such as aspiration pneumonia, suffocation, and eventually, premature death. The previous studies indicated a various range of prevalence of OD. The present systematic review and meta-analysis aimed to standardize the global prevalence of OD in different populations. Methods A systematic literature review was conducted using Embase, Scopus, PubMed, Web of Science (WoS) databases, and Google Scholar motor engine using related MeSH/Emtree and Free Text words, with no time limitation until November 2021. The heterogeneity among studies was quantified using I 2 index and the random effects model was used, due to the high heterogeneity among the results of studies included in the meta-analysis. Results The systematic literature search retrieved 2092 studies. After excluding the irrelevant studies, ultimately 27 articles with a sample size of 9841 were included in the meta-analysis. After combining the studies, the overall estimate of the global prevalence rate of OD was 43.8% (95% CI 33.3–54.9%) and the highest prevalence rate was estimated in Africa with 64.2% (95% CI 53.2–73.9%). Given the subgroup analysis based on the study population, the highest prevalence of OD was related to Dementia with 72.4% (95% CI 26.7–95.0%). The results of meta-regression indicated that the prevalence of OD has an increasing trend with the enhancement of year of publication and mean age. Conclusion The results of the present systematic review and meta-analysis revealed that the prevalence of OD is high in different populations and its trend has been increasing in recent years. Therefore, the appropriate strategies should be applied to reduce the prevalence of OD by finding its causation and monitoring at all levels, as well as providing feedback to hospitals.